Enrollment of adolescents and young adults onto SWOG cancer research network clinical trials: A comparative analysis by treatment site and era. (3rd February 2020) - Roth, Michael E.; Unger, Joseph M.; O'Mara, Ann M.; Lewis, Mark A.; Budd, Troy; Johnson, Rebecca H.; Pollock, Brad H.; Blanke, Charles; Freyer, David R.
Abstract: Background: Few adolescents and young adults (AYAs, 15‐39 years old) enroll onto cancer clinical trials, which hinders research otherwise having the potential to improve outcomes in this unique population. Prior studies have reported that AYAs are more likely to receive cancer care in community settings. The National Cancer Institute (NCI) has led efforts to increase trial enrollment through its network of NCI‐designated cancer centers (NCICC) combined with community outreach through its Community Clinical Oncology Program (CCOP; replaced by the NCI Community Oncology Research Program in 2014). Methods: Using AYA proportional enrollment (the proportion of total enrollments who were AYAs) as the primary outcome, we examined enrollment of AYAs onto SWOG therapeutic trials at NCICC, CCOP, and non‐NCICC/non‐CCOP sites from 2004 to 2013 by type of site, study period (2004‐08 vs 2009‐13), and patient demographics. Results: Overall, AYA proportional enrollment was 10.1%. AYA proportional enrollment decreased between 2004‐2008 and 2009‐2013 (13.1% vs 8.5%, P  < .001), and was higher at NCICCs than at CCOPs and non‐NCICC/non‐CCOPs (14.1% vs 8.3% and 9.2%, respectively; P  < .001). AYA proportional enrollment declined significantly at all three site types. Proportional enrollment of AYAs who were Black or Hispanic was significantly higher at NCICCs compared with CCOPs or non‐NCICC/non‐CCOPs (11.5% vs 8.8, P  = .048 and 11.5% vs 8.6%, P  = .03, respectively). Conclusion: Not only did community sites enroll a lower proportion of AYAs onto cancer clinical trials, but AYA enrollment decreased in all study settings. Initiatives aimed at increasing AYA enrollment, particularly in the community setting with attention to minority status, are needed. Abstract : From 2004‐2013, adolescents and young adults (AYA) proportional representation of AYAs on SWOG Cancer Research Network clinical trials decreased significantly across all treatment settings, including community‐based sites. Initiatives are needed to overcome barriers preventing limiting AYA trial enrollment.